Genetic evaluation of Ethiopian Boran cattle and their crosses with Holstein Friesian for milk constituent traits in central Ethiopia - Haile, Aynalem; Joshi, B.K.; Ayalew, W.; Tegegne, Azage; Singh, A.; Yilma, Z. (2008)
Breed additive and non-additive effects, and genetic parameters of milk fat, protein, solids not fat (SNF) and total solids (TS) percents, were estimated in Ethiopian Boran cattle and their crosses with Friesian in central Ethiopia. Ethiopian Boran cattle were consistently superior (P<0.01) to the Ethiopian Boran- Holstein Friesian crosses for the milk composition traits studied. When the crosses were compared, the fat, protein, SNF and TS percents of 50 and 62.5% Holstein Friesian crosses were higher (P<0.01) than those of 75 and 87.5% genetic groups. The 50 and 62.5% genetic groups did not differ (P>0.05) in milk constituents. It was apparent, therefore, that as the exotic gene level increased the percentages of the milk constituents declined significantly. The individual additive genetic breed difference for milk composition traits were all significant (P<0.01). The estimates were -1.45 for fat, -0.97 for protein, -1.13 for SNF and -2.47 for TS percents. Crossbreeding of the Holstein Friesian with the Ethiopian Boran resulted in desirable and significant (at least P<0.05) individual heretosis for all milk composition traits. The estimates were 0.54 ± 0.09, 0.25 ± 0.10, 0.33 ± 0.15 and 0.72 ± 0.18 for fat, protein, SNF and TS percents, respectively. The maternal heterotic effects were non-significant (P>0.05) for all traits except for fat percent. Heritabilities of fat, protein, SNF and TS percents for Ethiopian Boran were 0.49 ± 0.03, 0.26 ± 0.05, 0.46 ± 0.04 and 0.45 ± 0.04, respectively. The corresponding estimates for crosses were 0.32 ± 0.04, 0.49 ± 0.03, 0.39 ± 0.04 and 0.41 ± 0.04, respectively. Within Ethiopian Boran breed selection accompanied by crossing should enormously improve these traits in crossbreds under such production system.